A new dicynodont (Anomodontia: Emydopoidea) from the terminal Permian of KwaZulu-Natal, South Africa - Kammerer, Christian F. (Evolutionary Studies Institute, 2019)
A new taxon of dicynodont (Thliptosaurus imperforatus gen. et sp. nov.) is described based on a dorsoventrally-crushed skull from latest Permian (upper Daptocephalus Assemblage Zone) strata in KwaZulu-Natal, South Africa. Thliptosaurus is distinguished from all other dicynodonts by an elongate intertemporal bar with broad dorsal exposure of the parietals but apparently no pineal foramen. Absence of the pineal foramen in dicynodonts is exceedingly rare; the only other taxa which exhibit this feature either have substantially broader (Kawingasaurus fossilis) or narrower (Kombuisia frerensis) intertemporal regions. Inclusion of Thliptosaurus in a phylogenetic analysis of dicynodonts recovers it as a kingoriid emydopoid, a position supported by its anteriorly-restricted pterygoid keel, elongate, curved anterior process of the lacrimal, relatively posterior position of the median pterygoid plate, and occlusion of the mandibular fenestra by a lateral plate of the dentary. Intriguingly, even in the other kingoriids which retain a pineal foramen (Dicynodontoides spp. and Kombuisia antarctica), this structure is reduced in size relative to other dicynodonts, suggesting that the pineal eye was less important for thermoregulatory activity in this clade than in other anomodonts. Although part of a local fauna including taxa that are otherwise widespread in the Karoo Basin (Daptocephalus, Lystrosaurus), the unique presence of Thliptosaurus in the relatively poorly-sampled Daptocephalus Assemblage Zone deposits of KwaZulu-Natal suggests that this region may preserve endemic taxa, and should be prioritized for future fieldwork. Deutsche Forschungsgemeinschaft (KA 4133-1/1) JNC2019